Budaya Birokrasi dalam Konteks Transformasi Struktural: Antara Harapan dan Kenyataan - Moeljarto Tjokrowinoto (Magister Administrasi Publik, 1996)
The form bureaucracy in a country basically reflects the interaction between value premise and factual premise. An effort in the reformation administration, which in reality, is a process for manipulating several determinants of bureaucracy so that the entire components of bureaucracy will be oriented towards the objeaisw, which is intended to be shaped through the development process, all requires a lot of consideration on the determinants of bureaucratic reformation earlier on mentioned This is because it is necessary to realize that some determinants of bureaucratic reformation often times, pass by the structural-pracediral dimension, psychological dimendon, economic and stuctural dmention, cod finalty the cultural dimention. It is apparent that bureaucracy in Indonesia is signified by the coexistence between Weberian bireaucracy which onginatesfivm the west and the traditional bureaucracy which has its roots in the socio-cultural aspects of the place. With due consideration to the conditions which have been pointed out above, this writing suggests that the process of bureaucratic transformation is not only able to make an emphasis on the formal aspects of a modfying system. In order that the administration reformation must point out not only at the industrialization process, but also on the phenomenon or the shape of the industrial society with the values which arc inherent in that particular society.